Invited Editorial: Drilling for Micro-Foundations of Human Capital–Based Competitive Advantages - Coff, Russell; Kryscynski, David (Journal of Management, 2011)
From the origins of resource-based theory, scholars have emphasized the importance of human capital as a source of sustained competitive advantage, and recently there has been great interest in gaining a better understanding of the micro-foundations of strategic capabilities. Along these lines, there is little doubt that heterogeneous human capital is often a critical underlying mechanism for capabilities. Here, the authors explore how individual-level phenomena underpin isolating mechanisms that sustain human capital–based advantages but also create management dilemmas that must be resolved in order to create value. The solutions to these challenges cannot be found purely in generic human resource policies that reflect best practices. These are not designed to mitigate idiosyncratic dilemmas that arise from the very attributes that hinder imitation (e.g., specificity, social complexity, and causal ambiguity). The authors drill down deeper to identify individual- and firm-level components that interact to grant some firms unique capabilities in attracting, retaining, and motivating human capital. This cospecialization of idiosyncratic individuals and organizational systems may be among the most powerful isolating mechanism. The authors conclude by outlining a research agenda for exploring cross-level components of human capital–based advantages.